KEWENANGAN KEPALA DAERAH DALAM MENYELENGGARAKAN PENDIDIKAN DASAR TAHUN 2022 MENURUT PERATURAN DAERAH KABUPATEN SEMARANG NOMOR 12 TAHUN 2020 TENTANG PENYELENGGARAAN PENDIDIKAN: The Authority of The Regional Head in Organizing Basic Education In 2022, According to Regional Regulation of Semarang Regency Number 12 Of 2020 Concerning the Implementation of Education - Fauzi, Surya Triputra; Purnomowati, Reni Dwi (Faculty of Law, Universitas Trisakti, 2024)
Regional heads are the most important element in management at the regional level, especially in the field of education administration. To measure the implementation of education, it is necessary to have a legal basis, including Law no. 17 of 2010. One of the educational management is implemented in the district area. Semarang with Semarang Regency Regulation no. 12 of 2020. However, the implementation of education management in the Regency area. Semarang still needs to be explored further. So, the author is interested in further research regarding education management with the problem formulation: What is the authority of the regional head of Semarang district in implementing education according to Semarang Regency Regional Regulation No. 12 of 2020 concerning the Implementation of Education and whether the regional head of Semarang Regency has implemented the implementation of Education in Basic Education in accordance with Semarang Regency Regional Regulation No. 12 of 2020 concerning the Implementation of Education. The results of this research state that the Semarang regent is still not implementing education management optimally so that there is still a shortage of students and adequate facilities, as experienced at SDN Ngajaran